Language and linguistics the key concepts - Trask, R. L. (Robert Lawrence) 1944- (Routledge key guides, 2007)
A guide to the terms and concepts used in the study of language and linguistics. Definitions featured range from: terms used in grammatical analysis, and branches of linguistics from semantics to neurolinguistics, to linguistic phenomena from code-switching to conversational implicature, and, language varieties from pidgin to standard language